Physiologically‐Based Pharmacokinetic Modeling of the Drug-Drug Interaction of the UGT Substrate Ertugliflozin Following Co‐Administration with the UGT Inhibitor Mefenamic Acid - Ernesto Callegari; Jian Lin; Susanna Tse; Theunis C. Goosen; Vaishali Sahasrabudhe (Wiley, 2021)
The sodium‐glucose cotransporter 2 inhibitor ertugliflozin is metabolized by the uridine 5'‐diphospho‐glucuronosyltransferase (UGT) isozymes UGT1A9 and UGT2B4/2B7. This analysis evaluated the drug-drug interaction (DDI) following co‐administration of ertugliflozin with the UGT inhibitor mefenamic acid (MFA) using physiologically‐based pharmacokinetic (PBPK) modeling. The ertugliflozin modeling assumptions and parameters were verified using clinical data from single‐dose and multiple‐dose studies of ertugliflozin in healthy volunteers, and the PBPK fraction metabolized assignments were consistent with human absorption, distribution, metabolism, and excretion results. The model for MFA was developed using clinical data, and in vivo UGT inhibitory constant values were estimated using the results from a clinical DDI study with MFA and dapagliflozin, a UGT1A9 and UGT2B4/2B7 substrate in the same chemical class as ertugliflozin. Using the verified compound files, PBPK modeling predicted an ertugliflozin ratio of area under the plasma concentration-time curves (AUCR) of 1.51 when co‐administered with MFA. ClinicalTrials.gov identifier: NCT00989079.